2003
DOI: 10.1046/j.1444-2906.2003.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

A new device for monitoring the activity of freely swimming flatfish, Japanese flounder Paralichthys olivaceus

Abstract: The tail beat and activity behavior of four captive Japanese flounder Paralichthys olivaceus, were monitored with acceleration data‐loggers while the fish swam in an aquarium. Depth, swimming speeds and two‐axis acceleration data were collected continuously for approximately 20 h per fish. Simultaneously, the swimming behaviors of the fish were filmed at different angles. Using the specific characteristic of the acceleration profiles, in tandem with other types of data (e.g. speed and depth), four behavioral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 22 publications
2
48
1
Order By: Relevance
“…If a fish species that moves more in the vertical domain had been used, such as a cruise predator, we would expect vertical acceleration to make a greater contribution to the parameter set (e.g. Kawabe et al, 2003a). Fast-start event detection may be more complex if the vertical acceleration contribution to spontaneous movement increased, which could decrease the power of the standard deviation as a stand-alone detection parameter and thus other parameters may be required to detect fast-start events.…”
Section: Limitations On Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…If a fish species that moves more in the vertical domain had been used, such as a cruise predator, we would expect vertical acceleration to make a greater contribution to the parameter set (e.g. Kawabe et al, 2003a). Fast-start event detection may be more complex if the vertical acceleration contribution to spontaneous movement increased, which could decrease the power of the standard deviation as a stand-alone detection parameter and thus other parameters may be required to detect fast-start events.…”
Section: Limitations On Parametersmentioning
confidence: 99%
“…We neglected the statistical identification of simple locomotion, such as resting or swimming, because comparable acceleration studies in fish have shown that FFT analyses will detect and identify these movements (Kawabe et al, 2003a;Whitney et al, 2010).…”
Section: Limitations On Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Such data can be used to quantify variation in behaviour, energetics and habitat use and provide objective measurements of how animals interact with each other and respond to their environment [1]. Most recently, accelerometer sensors have been used for remote measurements of fine-scale movements among free-swimming fish [4][5][6] in controlled mesocosms [7][8][9][10][11], as well as in the wild [1, 4-6, 12, 13]. Typically, in situ measurements are collected using implanted archival tags or pop-up satellite tags (PSATs) that are deployed over weeks to years [14].…”
Section: Introductionmentioning
confidence: 99%